A rod‐ and tessellation‐based comparative analysis of polymorphic and structurally‐invariant molecular crystals: application to sulfathiazole and 2‐benzyl‐5‐benzylidenecyclopentanones. Issue 1 (12th January 2023) - Thomas, Noel W.; Hughes, David S.
Abstract : Four complementary analytical methods are applied to two direct opposites, a polymorphic organic compound and a set of relatively structurally invariant derivatives of a single compound. A general parameterization is proposed. Abstract : A rationalization of the alternative crystal structures adopted by a given molecular compound or by a set of substitutionally related molecular compounds is provided by reference to the five known polymorphs of sulfathiazole and 16 substituted 2‐benzyl‐5‐benzylidene cyclopentanones (BBCPs), respectively. Two‐dimensional (2D) packing fractions (ϕ2D ) take space‐group symmetry into account, with a clear demarcation of closed‐packed zones (CPZ) and molecular junction zones (JZ) in all Z ′ = 1 structures. Representation of the molecules as two linked rods allows a concise treatment of conformation and rapid visualization of crystal packing. Combined with calculations of intermolecular potential energies, the rod method provides insight into the stabilization mechanisms of alternative polymorphs. In sulfathiazole, the primary factor is to obtain satisfactory hydrogen bonding, with close packing a secondary consideration. In BBCP derivatives, by comparison, close packing is the primary mechanism of stabilization. Whereas the 2D structures arising in CPZ can be analysed as tessellations of molecular‐based cells, a method based on 2D Dirichlet cells is required for the JZ. These are calculated from the centroids of the molecular envelopes in high‐symmetry planes. It is shown that these centroid coordinates, when combined with space‐group symmetry and unit cell coordinates, provide a concise parameterization of all structures containing JZ. It is anticipated that this parameterization may be exploited to predict such crystal structures from powder diffraction data.